Brandmorphosis Analysis of Teh Botol Sosro - Asri Annisa Nasution; Eli Sulihtyaningrum; Rahma Dita Dewayani (Jobmark: Journal of Branding and Marketing Communication, 2025)
This article analyses the Brandmorphosis™ of Teh Botol Sosro, a packaged tea beverage product. The approach used is Brandmorphosis™ analysis, which focuses on the brand's journey, evolution, and metamorphotic narrative. The Brandmorphosis™ analysis emphasizes understanding the brand's journey through significant moments. Using archival and artefactual studies, the results of the analysis show that in Brandmorphosis™ Narrative Analysis (BNA), Brandmorphosis™ Transformative Analysis (BTA), and Brandmorphosis™ Retrospective Analysis (BRA), consistent values, product authenticity, and strategic positioning were identified as critical factors in Teh Botol Sosro's success. The lessons learned from this biographical lens of Teh Botol Sosro include the significance of maintaining consistent brand values, adapting to changing market demands, fostering social engagement, and leveraging historical moments for future growth and success.